The Combined Effect of Ethnic Identity Strength and Profiles on the Mental Health of Acadian University Students: A Portrait of New Brunswick’s Regions - Dupuis, Jérémie; Beaton, Ann (Minorités linguistiques et société / Linguistic Minorities and Society, 2018)
This two-part study aims to examine the moderating effect of ethnic identity strength on the relationship between ethnic identity profiles and mental health among Acadian university students who occupy a relative minority or majority status in the province of New Brunswick. Study 1 tested the factorial structure of an ethnic identity profile measure for Acadian students. Exploratory and confirmatory factor analyses supported a three-factor model, resulting in Affirmation, Detachment and Insecurity profiles. In Study 2, results of the moderation analysis revealed that the combination of a strong ethnic identity and an Affirmation profile provides protection against mental health issues for minority-status Acadian students, but not for majority-status Acadian students. Conversely, the combinations of a strong ethnic identity with the Detachment and Insecurity profiles increased the vulnerability of minority-status Acadian students to mental health issues, but not that of majority-status students.